Las cuentas por cobrar comerciales y su incidencia en los estados financieros en la Empresa Ferrecolor S.A. - Jaramillo Banchón, Wilson Julián (2024)
The objective of this research is to analyze the influence of commercial accounts receivable with accuracy and their impact on the financial statements of costs on the accuracy and transparency of the financial statements of Ferrecolor S.A. To fulfill this objective, the methodology used is a qualitative approach, descriptive scope, for the techniques and instruments, documentary analysis and interviews with two employees of the company Ferrecolor S.A. were used. Consequently, a proposal oriented to the training of the personnel, collection policies. For process control. These measures have the potential to optimize collection management and liquidity, as well as strengthen the competitive positionof Ferrecolor S.A. in the market.